2022
DOI: 10.4041/kjod22.118
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of bioactivity and osseointegration in Ti-6Al-4V orthodontic mini-screws coated with calcium phosphate on the TiO2 nanotube layer

Abstract: Objective This study evaluated the effect of cyclic pre-calcification treatment on the improvement of bioactivity and osseointegration of Ti-6Al-4V mini-screws. Methods The experimental groups were an untreated group (UT), an anodized and heat-treated group (AH), and an anodized treatment followed by cyclic pre-calcification treatment group (ASPH). A bioactive material with calcium phosphate was coated on the mini-screws, and its effects on bioactivity and osseointegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…On the other hand, MC3T3-E1 cells are frequently used for annealed TiO 2 nanotubes grown on commercially pure Ti alloys with no reports on unexpected cytotoxic effects [49,94,95]. Moreover, TiO 2 nanotubes produced on the surface of screws and implants of the Ti6Al4V alloy and annealed in similar conditions as described in this work, showed an enhanced bioactivity and osseointegration when implanted in vivo, with no cytotoxic effects [96][97][98]. Human body fluids are rich in organic substances of low molecular weight and polymeric compounds of relatively high molecular weight, such as amino acids, soluble proteins, and traces of cellular debris that may have a role in the concentration of metal ions in the vicinity of the implant.…”
Section: Cytocompatibility Evaluation and Ion Releasementioning
confidence: 57%
“…On the other hand, MC3T3-E1 cells are frequently used for annealed TiO 2 nanotubes grown on commercially pure Ti alloys with no reports on unexpected cytotoxic effects [49,94,95]. Moreover, TiO 2 nanotubes produced on the surface of screws and implants of the Ti6Al4V alloy and annealed in similar conditions as described in this work, showed an enhanced bioactivity and osseointegration when implanted in vivo, with no cytotoxic effects [96][97][98]. Human body fluids are rich in organic substances of low molecular weight and polymeric compounds of relatively high molecular weight, such as amino acids, soluble proteins, and traces of cellular debris that may have a role in the concentration of metal ions in the vicinity of the implant.…”
Section: Cytocompatibility Evaluation and Ion Releasementioning
confidence: 57%
“…In the remaining 14 studies, differences were found between the stability of the machined surface and other surface treatments [27,28,30,[33][34][35][36]38,39,[41][42][43]. Unlike other acid-etched studies, Jang et al [33] immersed miniscrews with acid-etched surfaces in calcium chloride solution.…”
Section: Main Study Outcomementioning
confidence: 99%
“…Compared to the control group, MRT values measured at 3 and 6 weeks were higher in the surface treatment group. Byeon et al [35] evaluated the contribution of cyclic precalcification treatment to osseointegration and the bioactivity of miniscrews. The experimental groups of this study were as follows: anodized and heat-treated group; anodized, heat-treated and cyclic pre-calcification treatment group; and control group.…”
Section: Main Study Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The addition of TiO 2 can stabilize the phosphate lattice of calcium phosphate materials. It has been reported that TiO 2 can improve chemical stability and module of elasticity and increase the viscosity of calcium phosphate systems. …”
Section: Introductionmentioning
confidence: 99%